Impact of Foreign Migration on Cultivable land of Phalgunanda Rural Municipality Ward No. 4, Panchathar Nepal - Karki, Prem Bahadur (Rupantaran: A Multidisciplinary Journal, 2025)
Nepal is one of the countries most influenced by foreign migration not only in Asia, but globally. This study focused on foreign migration and how to affects the use of cultivable land in the eastern hilly site of Nepal. The main objectives of this study are to identify the condition and use of cultivable land and the identification of major reason for not using cultivable land. The nature of analysis is quantitative including descriptive design. Similarly, most of the data used in this study are accumulated based on primary data collection procedure. Most of the migrant’s population are preferred in Malaysia as a destination. Most of the migrant’s population are found in the age group 25-34 years. Eighty five percent (221) have had cultivable land and only 15 percent have had not had cultivable land. But there was land that could not be used for cultivation. Majority of the migrants’ households (62.9%) have been utilizing their land and 37.1 percent have not been utilization of cultivated land. Out of total household are not utilizing land for cultivation, more than 76 percent households have not been utilizing their cultivated land due to lack of working member of family. Out of 63 household, more than 77 percent (49) of households are found the cause of not enough member of household due to foreign employment for cultivation. It was noted that while all migrant households in the study area had land. Why is the number of people going other countries? It seems necessary to research for it. Therefore, there is need for the local government to formulate various policy and programs related to the quality of life in order to minimize the trend of foreign employment in this sector. While formulating local policies and programs, local knowledge and skills should not be forgotten.